Analysis of the Effectiveness of Using Flipbook-Based E-Modules in Science Learning in Elementary Schools - Ida Puspita Sari; Rohmani Rohmani; Khoirun Nisa’ (IJORER : International Journal of Recent Educational Research, 2024)
Objective: Science learning in elementary school is essential in building scientific understanding and positive attitudes towards science in students. This study aims to analyze the effectiveness of using flipbook-based e-modules in learning science in elementary school. Method: The method used in this research is a systematic literature review that includes various relevant empirical studies from 2019 to 2023. Data sources were collected from academic databases such as Google Scholar using the keywords e-module, flipbook, science, and elementary school. Results: The results of the analysis show that using flipbook-based e-modules in learning science in elementary schools has several advantages, including increased student learning motivation, better interaction between students and materials, and improved mastery of science concepts. Novelty: This research contributes to developing engaging and effective learning methods in primary education and encourages further research to explore the long-term impact of using flipbook-based e-modules in various teaching contexts.